A newly recorded gobiid genus, Discordipinna (Teleostei: Gobiidae), from northeastern Taiwan - Chou, Li-Chin; Jiang, Guo-Chen; Shen, Kang-Ning (Zootaxa, 2024)
A specimen of the newly recorded gobiid genus Discordipinna was recently collected from northeastern Taiwan via SCUBA diving. The newly recorded spikefin goby, Discordipinna griessingeri Hoese & Fourmanoir, 1978, is the type species of the genus. The sole specimen was collected from Longdong Bay, northeastern Taiwan, and it closely matches the original description of the species. The redescription of this extremely rare reef goby species found in Taiwanese waters is diagnosed and reported in this paper.